Factors influencing Recidivism Drug Abuse among Probationers in Kalasin Province: Factors influencing Recidivism Drug Abuse among Probationers in Kalasin Province - Purichonpituk , Amorntep; Kenaphoom, Sanya; Phosing, Phakdee (RATANABUTH JOURNAL, 2024)
This research aims to (1) study the level of recidivism involving drug abuse among offenders under supervision in Kalasin Province, (2) investigate the factors influencing recidivism involving drug abuse among probationers in Kalasin Province, and (3) propose recommendations for preventing recidivism involving drug abuse among probationers in Kalasin Province. The sample group consists of 184 probationers ordered by the court to undergo supervision for drug-related offenses at the Kalasin Provincial Probation Office. The research utilized Taro Yamane’s formula as well as statistical tools including percentages, means, frequencies, standard deviations, and multiple regression analysis. The research findings indicate that (1) the level of recidivism involving drug abuse among probationers in Kalasin Province is moderate. Upon further examination, (2) factors influencing recidivism include personal factors (β = 290), drug potency (β = .270), and socio-environmental factors (β = .164) which collectively predict 46.80% of the variance significantly at the .05 level. Additionally, and (3) recommendations for preventing recidivism involving drug abuse among probationers include raising awareness about the dangers of drug abuse, enhancing drug education in schools and public health agencies, which are crucial factors in preventing and addressing drug-related issues in society. Family and community support play pivotal roles in reducing drug-related problems in society. Strengthening policies and regulations to control the production, import, and distribution of drugs, as well as law enforcement and legal measures to improve drug control, are essential. Moreover, bolstering counseling and treatment services tailored to drug users’ needs and establishing effective rehabilitation and recovery systems are crucial for successful intervention.